Systematic literature review: mathematical creative thinking ability reviewed from self-regulated in Project Based Learning (PjBL) Model - Nurfaidah, Nurfaidah; Pujiastuti, Emi; Nur Cahyono, Adi; Sugiman, Sugiman; Kharisudin, Iqbal; Korkor, Sarah (Nashir Al-Kutub Indonesia, 2023)
In learning mathematics to solve problems, students must own creativity and finish independently. Creativity and study in a manner independence can be increased by applying a learning model. Study This own The aim is to conduct a literature review regarding the based learning model project to improve the ability to think creatively mathematically and self-regulated or learn from students independently. The research method used is Systematic Literature Review (SLR) method. Selected articles based on quality, suitability, and suitability content so that obtained 17 articles from google scholar journals, national and international, in the range period 2017 to the year 2023. The research results obtained: (1) the PjBL learning model in learning mathematics can improve the ability to think creatively student, (2) independence influences learning on creative thinking skills.